2014
DOI: 10.1186/2046-0481-67-16
|View full text |Cite
|
Sign up to set email alerts
|

High level of treatment failure with commonly used anthelmintics on Irish sheep farms

Abstract: BackgroundIn 2013 a Technology Adoption Program for sheep farmers was established to encourage the implementation of best management practices on sheep farms in Ireland. There were 4,500 participants in this programme in 2013. As part of this programme, farmers had the option to carry out a drench test to establish the efficacy of their anthelmintic treatment.ResultsFlock faecal samples were collected before and after treatment administration and gastrointestinal nematode eggs enumerated. In total there were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Insufficient data were available to estimate mean prevalence for other anthelmintic classes and cattle. The prevalence of AR has also been estimated elsewhere, for example, treatment failure has been identified on 51 per cent of Irish sheep farms surveyed (Keane and others 2014) and 64 per cent of Scottish sheep farms surveyed (Bartley and others 2003). These studies provide valuable prevalence estimates, but the differences in sample (farm) selection methods introduce potential sample selection bias and may affect estimates and comparability between regions.…”
mentioning
confidence: 98%
“…Insufficient data were available to estimate mean prevalence for other anthelmintic classes and cattle. The prevalence of AR has also been estimated elsewhere, for example, treatment failure has been identified on 51 per cent of Irish sheep farms surveyed (Keane and others 2014) and 64 per cent of Scottish sheep farms surveyed (Bartley and others 2003). These studies provide valuable prevalence estimates, but the differences in sample (farm) selection methods introduce potential sample selection bias and may affect estimates and comparability between regions.…”
mentioning
confidence: 98%
“…For example, in the UK, Bartley et al (2006) observed a similar range of low efficacy of IVM (66% to 92% of egg reduction) in 6 of 17 naturally grazing flocks in south/central Scotland. Moreover, in a largescale survey, Keane et al (2014) observed low efficacy of macrocyclic lactones in 24% of 1308 studied farms in Ireland. This is in contrast with data obtained in some Mediterranean climates such as in Campania region (southern Italy) where all tested anthelmintic drugs including IVM remained totally effective (Rinaldi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing issues of anthelmintic resistance (AR) are encountered in tropical countries (Almeida et al 2010;Mahieu et al 2014), but recent studies demonstrated that most European countries were more and more facing this issue (Rose et al 2015). In almost all sheep markets in Europe, AR to benzimidazoles (BZ) has been described (Papadopoulos et al 2012); however, ivermectin (IVM) and moxidectin (MOX) resistances are still less frequent in Europe than in the southern hemisphere with the noticeable exception of the UK (Bartley et al 2006) and Ireland (Keane et al 2014). BZ resistance has been frequently described in mainland France (Chartier et al 1998;Geurden et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…; Keane et al . ). Selective breeding for resistance to nematode infection is a complementary and sustainable method for controlling the effects of nematodes on ruminants (Riggio et al .…”
Section: Details Of Genomic Regions Validated In Sheep Populations Inmentioning
confidence: 97%